Clinical characteristics and distinct recovery trajectories of pain and disability after lumbar microdiscectomy in children and adolescents - Muhammed Erkan Emrahoğlu; Mustafa Kavcar; Erdal Reşit Yılmaz; Hüseyin Bozkurt; Mehmet Kalan; Ahmet Günaydın; Hakan Yakupoğlu; Halil Gök; Levent Gürses; Emrah Keskin; Selim Gel; Mehmet Erhan Türkoğlu (Frontiers in Surgery, 2026)
Background Pediatric and adolescent lumbar disc herniation (LDH) is uncommon, and recovery after microdiscectomy may differ across pain, disability, and outcome domains. Methods This retrospective single-center case series included patients younger than 18 years of age who underwent microdiscectomy for LDH between 2022 and 2025 and had complete 12-month outcome data. Low back and radicular leg pain were assessed using the visual analog scale (VAS), disability using the Oswestry Disability Index (ODI), and global outcome using the modified MacNab criteria. Longitudinal changes were analyzed using Friedman tests and Holm-adjusted pairwise comparisons. A post hoc responder analysis applied adult-derived absolute thresholds and a reduction of at least 30%. Results Seventeen patients were included (median age, 16 years; median follow-up, 21 months). The median low back pain VAS score increased from 4 preoperatively to 7 early postoperatively and then decreased to 1 at 3 and 12 months (overall p < 0.001). The median radicular leg pain VAS score decreased from 8 preoperatively to 2 early postoperatively and 1 at 3 and 12 months (overall p < 0.001). The median ODI score decreased from 50 preoperatively to 12 at 3 months and 6 at 12 months (overall p < 0.001), with further improvement between 3 and 12 months ( p < 0.05). All evaluable patients met both responder criteria from baseline to 3 and 12 months. Modified MacNab categories did not change significantly ( p = 0.313). No complications occurred; two patients developed recurrence and one underwent reoperation. Conclusions Pain, disability, and global outcome followed distinct trajectories. These exploratory findings support separate assessment of recovery domains and require confirmation in larger multicenter cohorts.